Pemberdayaan Ekonomi Keluarga Dengan Digital Marketing - Nico Lukito; Febria Nalurita; Hartini (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
Community Service activities aim to support the improvement and empowerment of family economic activities in increasing participants' understanding and awareness of the importance of how to utilize digital marketing to expand marketing. Islamic Entrepreneurship Boarding School (IEBS) Purwakarta, a school under the Global Cahaya Nubuwwah Insani (GCNI) Foundation which is located at Tegal Sapi, Neglasari Village, Darangdan District, Purwakarta Regency, West Java. The participants who participated in this activity both students and students totaled 42 people. Most participants are between 16-19 years old, which by looking at this age is very productive and has the potential to develop the family economy in utilizing digital marketing. The business run by parents is a trading business that has been registered in an online store and has used the most digital marketing using Whatssap. The counseling and training participants received direct benefits, increased their knowledge and were very satisfied with the activities.